Electronic comerce a management perspective - Turban, Efrain; King, David; Lee, Jac (New Jersey: Prentice-Hall,Inc., 1999)
Contents: 1. foundations of electronic commerce; 2. retaiding in electronic commerce; 3. internet consumer and market reseach; 4. advertisiment in electronic commerce; 5. electronic commerce for service industries; 6. bussiness-tobusiness electronic commerce; 7. intranet and extranet; 8. electronic payment systems; 9. strategy and implementation; 10. public policy from legal issues to privacy; 11. infrastructure for ec. economics global, and other issues in ec; 12. creating web pages; 13. web programming: adding desktop interactivity and dinamic data access...
References p. 462 Glosary p. 505
Keywords: Electrónico Comercio